Determination of Rebaudioside A in Mixed beer, Beer-based Beverages and Lemonades - Jurková, Marie; Olšovská, Jana (KVASNY PRUMYSL, 2015)
The plant Stevia rebaudiana (Stevia sweet) is becoming a favourite sweetener in the food industry. Sweet taste is caused by diterpenic glycosides, so-called steviol glycosides, which lack calories while being 300 times sweeter than sucrose. While all the other glycosides are slightly or even disagreeably bitter, rebaudioside A possesses desirable sensorial properties. Because this sweetener is used to sweeten beverages including mixed beer, a fast routine analytical method was developed using HPLC with UV detection for determination of rebaudioside A in mixed beer and lemonade. The HILIC principle, which is suitable for separation of polar and hydrophilic analytes, was used for separation of steviol glycosides. The method is selective, reproducible and has a high recovery of 90–100 %.